PENGARUH MODEL PEMBELAJARAN TGT BERBANTUAN POP-UP BOX PADA MATERI GAYA TERHADAP HASIL BELAJAR SISWA KELAS IV DI SDN 1 MAJAN - Anisa Hanna Alhayah; Aldila Wanda Nugraha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to find out whether or not there is an effect of the Pop-Up Box-assisted TGT learning model on style materials on the learning outcomes of grade IV students. This type of research is an experiment. The design used in the study is Pre-Experimental Design using the One Group Preetest-Posttest Design research design. This design was carried out to compare the results of pre-test before being treated using TGT-based pop-up box learning media on style material and post-test after being treated. Judging from the Paired Sample t-test with the analysis results, it was shown that the experimental class had a Sig. value of 0.000 and this value was smaller than 0.050 (0.000< 0.050), so it was concluded that there was a significant difference between the learning outcomes before being given the TGT learning model and after being given the TGT learning model. Based on the results of the analysis, it is known that the TGT learning model has an effect on learning outcomes. Keywords: ipas, learning outcomes, pop-up box, tgt model